Motivational Factors in the Perception of Psychological Situation Characteristics. Issue 2 (February 2016) - Rauthmann, John F.
Abstract: This article seeks to formulate how motivational factors underlie and contribute to situation perceptions. Specifically, it is proposed that situation perceptions, to a large extent, capture subjectively perceived "motivational presses", consisting of motivational processes (What happens to one's needs and goals in the situation?) and motivational content (Which needs or goals does the situation concern?). Additionally, such a motivational perspective can be fruitfully equipped with evolutionary psychological theories on human (social) motives. Thus, it is argued that situation perception contains evolutionarily important information on motivational processes and content. An evolutionarily informed motivational perspective on situation perception is applied to the recently proposed Situational Eight DIAMONDS situation characteristics to provide them with a theoretical underpinning. Ultimately, such a framework can be used to better understand situations and person–situation transactions (i.e., how people experience and shape situations in daily life) that can impact well‐being, health, and personality development.